Effect of calcium/sodium ion exchange on the osmotic properties and structure of polyelectrolyte gels. (December 2015) - Horkay, Ferenc; Basser, Peter J; Hecht, Anne-Marie; Geissler, Erik
We discuss the main findings of a long-term research program exploring the consequences of sodium/calcium ion exchange on the macroscopic osmotic and elastic properties, and the microscopic structure of representative synthetic polyelectrolyte (sodium polyacrylate, (polyacrylic acid)) and biopolymer gels (DNA). A common feature of these gels is that above a threshold calcium ion concentration, they exhibit a reversible volume phase transition. At the macroscopic level, the concentration dependence of the osmotic pressure shows that calcium ions influence primarily the third-order interaction term in the Flory–Huggins model of polymer solutions. Mechanical tests reveal that the elastic modulus is practically unaffected by the presence of calcium ions, indicating that ion bridging does not create permanent cross-links. At the microscopic level, small-angle neutron scattering shows that polyacrylic acid and DNA gels exhibit qualitatively similar structural features in spite of important differences (e.g. chain flexibility and chemical composition) between the two polymers. The main effect of calcium ions is that the neutron scattering intensity increases due to the decrease in the osmotic modulus. At the level of the counterion cloud around dissolved macroions, anomalous small-angle X-ray scattering measurements made on DNA indicate that divalent ions form a cylindrical sheath enveloping the chain, but they are not localized. Small-angle neutron scattering and small-angle X-ray scattering provide complementary information on the structure and interactions in polymer solutions and gels.